Analisis Keseimbangan Desain Interior Perpustakaan Sebagai Sarana Edukasi Siswa Pada Perpustakaan SMK Negeri 1 Trenggalek - Linda Lailatul Nur Hanifah; Arin Prajawinanti (Media Pustakawan, 2022)
The library of SMKN 1 Trenggalek is one of the important aspects in every academic learning activity, because it is a source of learning references. In order to make the library more attractive, the library building is arranged in such a way as to meet the needs of its users. The library space is a contributing factor to the smooth implementation of the library manager's duties. Without adequate space, library work cannot run well. This study attempts to analyze the balance of interior design of the SMKN 1 Trenggalek library as a means of educating students. The existence of this research is to find out the interior of the library and the role of the SMKN 1 Trenggalek library as a means of educating students. The research method used is descriptive qualitative through observation, interviews and documentation. The data obtained in this study include primary data and secondary data presented in narrative form. The results of this study found that the library of SMKN 1 Trenggalek applies an attractive modern concept library interior design according to the wishes of students. From this modern concept, it can be an attraction for students to visit the library to conduct knowledge and information search activities in learning at school that are not obtained in class. Hence, the practical application of the existing library interior design has played a role as a means of educating students in attracting students to always visit the library which makes the number of users increase and the library can function at its best.